ANALISIS OTOMASI SEBAGAI PENGENDALI PENGURUSAN SURAT DI SKPD PROVINSI JAWA TENGAH - Didik Singgih Hadi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
This study aims to determine how much influence the ease of automation as obtaining affect SKPD Central Java Province in dealing with the maintenance of the letter. The research method used by the population approach is to record the entire SKPD and the Bureau which were in Central Java Provincial Government totaling 58 institutions using the questionnaire Likert scale with 5 levels. From the results of the questionnaire as many as 67 questions were sent to 58 SKPD and Bureau in Central Java province early October 2016 as respondents were closed and processed data on October 12, 2016 responded to 54 respondents. 43 respondents answered by stating the name of the letter along with the name board SKPD / bureau, 7 respondents answered the questionnaire anonymously board letter and name of SKPD / bureau, 4 respondents did not answer the questionnaire (just send a blank questionnaire returned). One respondent issued from the population because they are outside SKPD / Bureau of Central Java province. So the data is processed with valid there were 42 respondents with identity and 7 respondents without identity.. The data is processed directly by the facility "GOOGLE FORMS" once used to distribute the questionnaire to all (58) SKPD / Bureau. Board letter understand and implement the decision of the Head of Archives and Library Agency Central Java Province No. 048/2143 of 2008 on Guidelines Active Archive Applications . Board letter so requires the availability of a computer and a scanner in the execution of works. Board felt the letter simply performing the task with an active archive applications. Board letter ease of control felt the existence of the letter in the execution of work, decision of the Head of Archives and Library Agency Central Java Province No. 048/2143 of 2008 on Guidelines Active Archive Applications To have equal legal force, efforts to regulation. Computer and scanner devices required in the implementation of the maintenance of the letter in SKPD. the need for reward for the management letter.